THE IMPACT OF ORGANISATIONAL INNOVATION ON THE FINANCIAL SUSTAINABILITY OF NON-GOVERNMENTAL ORGANISATIONS OPERATING IN UGANDA - Pulakkal, Nandanan Kannan (Digital Repository of Theses - SSBM Geneva, 2023)
NGOs play a pivotal role in Sub-Saharan Africa in the development and humanitarian fields, primarily where governments cannot fully provide for their citizens. NGOs have contributed to Uganda’s social, economic and political development. However, financial sustainability has been a critical challenge the NGOs face in fulfilling their role. The research investigated the relationship between organisational innovation and the financial sustainability of NGOs operating in Uganda. The study examined the impact of organisational innovations in corporate governance, financial management, external relations, and human resources management on the financial sustainability of the NGOs operating in Uganda. The study followed a mixed research method, using quantitative and qualitative approaches to obtain the required information. The researcher interviewed eight top management executives and analysed 102 responses to the online survey questionnaire received from staff in the middle and top management levels of NGOs operating in Uganda. The findings showed that organisational innovation in NGOs operating in Uganda was conceptualised as doing things in new ways and implementing new ideas and processes to improve s efficiency and effectiveness. Financial sustainability was conceptualized as an NGO’s ability to secure financial resources to implement its interventions over a long period without frequently depending on the donors. A strong significant positive relationship exists between corporate governance, financial management practices, external relations and human resource management practices and financial sustainability. Collectively, the predictor variables explain 45.1% of the variation in the financial sustainability of NGOs operating in Uganda. The study recommends that the donor community, NGOs and government promote organisational innovations to improve the financial sustainability of NGOs. NGOs should train staff in resource mobilization and strengthen their corporate governance, financial management practices and networking to diversify funding sources and improve financial sustainability. This research contributes to a better understanding of the impact of organisational innovations on the financial sustainability of NGOs, a grey area in the East African region. Further research is recommended with a wider scope covering all countries in the East African region is recommended for better generalisability.